High Thyroglobulin Antibody Levels Increase the Risk of Differentiated Thyroid Carcinoma. (27th October 2015) - Qin, Jing; Yu, Zhenqian; Guan, Haixia; Shi, Liangfeng; Liu, Yongping; Zhao, Na; Shan, Zhongyan; Han, Cheng; Li, Yushu; Teng, Weiping
Abstract : Background . Despite the many studies examining thyroid cancers, the effect of thyroid autoantibodies on differentiated thyroid carcinoma (DTC) remains unclear. Objective . To investigate the association between serologic thyroid autoantibodies (ATAs) and DTC, we retrospectively evaluated data of thyroid nodules obtained from patients who underwent thyroid surgery. Methods . Data of thyroid nodules obtained from 1, 638 patients who underwent thyroid surgery were evaluated. Thyroid autoimmunity was assessed by the presence of thyroglobulin (TgAb) or thyroid peroxidase antibodies (TPOAb). Results . Among our study cohort, the prevalence of elevated TgAb (≥40 IU/mL) and TPOAb (≥50 IU/mL) was higher in patients with DTC than those with benign nodules. Patients with DTC and elevated TgAb had a higher prevalence of extrathyroidal invasion. In the multivariate analysis, TgAb ≥ 40 IU/mL was significantly associated with DTC (odds ratio [OR] = 2.10, 95% confidence interval [CI] 1.40–3.15) compared with TgAb < 40 IU/mL group, independent of other confounding factors such as decreased age, single nodule, and elevated TSH level. In conclusion, elevated TgAb was associated with DTC. Conclusions . This study revealed that high levels of TgAb may act as an independent prediction factor for DTC, and suggests that patients with high TgAb concentrations may be predisposed to DTC.